Steering Control of an Underwater Vehicle using Adaptive Back Stepping Approach - Satti, Abdul Baseer; Nadeem, Faisal (Journal of Vibration Testing and System Dynamics, 2026)
This paper presents a simple and systematic approach to steer an underwater vehicle model by considering two different cases: (i) when all actuators are functional, and (ii) when one actuator is not working. In first case, the model of an underwater vehicle is steered by using adaptive Backstepping technique. The first actuator is necessary for the operation of the system so any of the other three actuators can be non-operational. So, the second case itself contains three different cases. Adaptive Backstepping is then used to steer the system with one non-working actuator. The synthesis method is general, in that it applies to a large class of drift free, completely controllable systems, for which the associated controllability Lie algebra is locally nilpotent.